1988
DOI: 10.1017/s0043174500075433
|View full text |Cite
|
Sign up to set email alerts
|

Factors Limiting the Distribution of Cogongrass,Imperata cylindrica, and Torpedograss,Panicum repens

Abstract: Greenhouse, growth chamber, and laboratory studies were conducted to determine anatomical and morphological characteristics and cultural practices limiting the distribution of cogongrass, torpedograss, and johnsongrass in the United States. Cogongrass did not produce axillary buds along most of the rhizome nor regenerate when apical six-node-long rhizome segments were buried deeper than 8 cm. Both torpedograss and johnsongrass produced axillary buds along the entire lengths of their rhizomes. Torpedograss shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
0
40
1
Order By: Relevance
“…In experimental trials, cogongrass was shown to out-compete and displace bahiagrass (Paspalum notatum) seedlings, but was not able to colonize established bahiagrass stands . Additionally, it has been demonstrated that cogongrass inhibits bermudagrass (Cynodon dactylon) growth, but was less competitive than Johnsongrass (Sorghum halepense) (Wilcut et al, 1988). Competition studies utilized a combination of greenhouse, growth chamber, and natural areas settings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In experimental trials, cogongrass was shown to out-compete and displace bahiagrass (Paspalum notatum) seedlings, but was not able to colonize established bahiagrass stands . Additionally, it has been demonstrated that cogongrass inhibits bermudagrass (Cynodon dactylon) growth, but was less competitive than Johnsongrass (Sorghum halepense) (Wilcut et al, 1988). Competition studies utilized a combination of greenhouse, growth chamber, and natural areas settings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is a prolific seeder, producing as many as 3,000 seeds per plant (Holm et al 1977). Whether by seed or by rhizome, I. cylindrica can invade a variety of ecosystems from xeric uplands to shaded mesic sites (Jose et al 2002;Ramsey et al 2003) regardless of soil conditions, mostly favoring acidic soils (Wilcut et al 1988;Collins et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Although torpedograss is typically found in moist, sandy soils, it has been reported to grow on heavy upland soils (12,25,28). Environmental conditions such as acidic soils and occasional flooding do not appear to negatively affect torpedograss growth (28).…”
Section: Torpedograss Infestation Of Warm‐season Turfgrassesmentioning
confidence: 99%
“…Poor torpedograss seed viability may indicate dissemination occurs primarily through vegetative propagation of rhizome‐contaminated soils (22,28). Torpedograss’ regenerates from rhizome fragments high in carbohydrate reserves (19,28). The rapid growth of torpedograss is capable of producing dense rhizome systems within a few months under favorable growing conditions (7).…”
Section: Torpedograss Infestation Of Warm‐season Turfgrassesmentioning
confidence: 99%
See 1 more Smart Citation